Hukum zakat : Studi Komperatif Mengenai Status dan Filsafat Zakat Berdasarkan ... - QARDAWI, Yusuf; Harun, Salman; Hafidhudhin, Didin; Hasanuddin (Pustaka Litera Antar Nusa, 2002)
xxvii, 1186 hlm.;23 cm.